Properties Of Hybrid Plywood From Oil Palm Trunk (OPT) Veneer And Empty Fruit Bunches (EFB) Mat - Rawi, Nurul Fazita Mohammad (2010)

(untitled)
Shortage of wood as a raw material has coerced wood based industries to find alternative local raw materials, and oil palm biomass appears as the most viable alternative. This work was based on the studies of converting oil palm trunk (OPT) and oil palm empty fruit bunches (OPEFB) into new plywood and to analyze their properties. Five-ply hybrid plywood (oil palm trunk veneer and empty fruit bunch mat was arranged alternately) with different spread levels (300 g/cm2 and 500 g/m2) of resins (phenol formaldehyde and urea formaldehyde) were prepared. The mechanical, physical and thermal properties of the plywood were studied.